Kraftkonstanten des V0₄³⁻-Ions im Zirkon-Gitter - Escobar, Marta E. (1980)
The force constants for the V0₄³⁻-ion present in the different rare earth orthovanadates of the zircon type have been computed using a modified valence force field and recently reported Raman data. It is shown that the V-0 bond strenghtening runs parallel to the unit cell contraction. The Raman spectrum of the tetragonal modification of LaV0₄ is reported for the first time.